ELABORATION, NUTRITIONAL AND SENSORY ANALYSIS OF PEANUT BUTTER FLAVORED WITH MOZZARELLA CHEESE - Resosemito , Franky Soedirlan; da Silva, Wendel Jefferson Reis; Leal, Edney Harrison Ferreira; Schmid, Giselle; Filho, Hostilio Caio Pereira da Costa; dos Santos, Elisvanda Ramos (Seven Editora, 2024)
Peanuts are one of the foods that are linked to the northeastern culture of Brazil. The consumption of this legume varies from the seed in natura, roasted and salted, to sweet (such as the traditional northeastern paçoca), in addition to derived products that have peanuts in their formulation. However, there is still the possibility of adding value and innovation using peanuts, since food industries are always looking for innovative products that are healthier. According to this, peanut butter is an excellent alternative, as it is a peanut-based product well accepted by a large part of the population, and is consumed by all social classes and age groups, in addition to being a very rich food in nutritional terms. Peanut butter can also be supplemented with other foods, in order to increase its nutritional and sensory values. Aiming at this aspect, the use of cheese as an alternative to supplement peanut butter is a viable option, since it is a food much appreciated by the Brazilian population due to its sensory and nutritional characteristics. In this sense, the present work aims to make peanut butter with cheese using the following ingredients: peanuts, mozzarella cheese, vegetable oil and salt. The nutritional composition and sensory evaluation of peanut butter enriched with mozzarella cheese were analyzed in order to ascertain the public's acceptance and purchase intention. In the present study, five peanut butter formulations were elaborated, ranging from 0, 10, 15, 20 and 25% mozzarella cheese, respectively. It was observed that the greater the amount of mozzarella cheese added to peanut butter, the less energetic the product is made. According to the results obtained, it is possible to conclude that the peanut butters enriched with mozzarella cheese did not reach the minimum result in relation to all the parameters analyzed (appearance, color, texture, flavor and global acceptance) with the average 7 (seven) being the minimum expected result. It is noteworthy that sample E with 35% mozzarella cheese was the one that came closest to the minimum sensory requirements, while for the intention to purchase sample C with 25% mozzarella cheese. That said, it is noticeable the need for a better adaptation in the formulation or addition of extra components that increase the sensory qualities of the product, it is also notorious that the product developed is unusual to the Brazilian palate, thus causing a high deviation in relation to sensory requirements. DOI:https://doi.org/10.56238/sevened2024.031-078